EPALE Conference: The Second Forum of Adult Education, Warsaw, 21.11.2017 - Marzena Indra; Jakub Kozłowski; Agata Poczman; Karolina Milczarek; Wojciech Zawadzki; Iwona Buks (Wydawnictwo Naukowe Uniwersytetu Mikołaja Kopernika, 2018)
Reports